A new sensing material design based on chemically passivated phosphorene/porous two-dimensional polymer: Highly sensitive and selective detection of NO2 - Tang, Yanting; Yang, Kai; Hua, Zhongqiu; Yin, Fuxing; Yuan, Wenjing (Sensors and actuators. B, Chemical, 2021)
[Display omitted] •A new gas sensing material was designed based on CPP/T-2DP.•Sensitivity of CPP/T-2DP improved by over 5-fold compared with phosphorene.•An enhancement mechanism was proposed for the highly sensitive NO2 detection.•The nanospacer intercalation strategy can be extended to other 2D sensing materials. Phosphorene has recently been receiving attention for gas sensing due to its unique geometric and electronic structure. However, several challenges still remain that hinder the potential application of phosphene, especially its ambient instability and sheets restacking during sensing film formation. Herein, we report on a new sensing material design based on incorporating chemically passivated phosphorene (CPP) with porous triazine-based two-dimensional polymer (T-2DP). The T-2DP nanosheets could act as nanospacers to prevent the dense stacking of phosphorene layers whilst providing abundant pathway for penetration and adsorption of gas molecules. Such CPP/T-2DP nanocomposite exhibited extended ambient stability, improved sensing speed, excellent selectivity and good flexibility for NO2 detection. The sensitivity of the nanocomposite sensor improved by over 5-fold in comparison with pristine phosphorene (2410 % for the nanocomposite vs 400 % for pristine phosphorene at 1 ppm of NO2). An enhancement mechanism for the CPP/T-2DP nanocomposite was proposed for the highly sensitive NO2 detection. In addition, this nanospacer intercalation strategy can be extended to other two-dimensional gas sensing nanomaterials, e.g. RGO. These results could provide inspirations in the design of two-dimensional sensing materials/composites and improve their prospects for wearable electronic applications.